2023
DOI: 10.3390/toxics11020092
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and Cytotoxicity to GC-2spd(ts) Cells of PM2.5 in Nanjing Jiangbei New Area from 2015 to 2019

Abstract: PM2.5 is an air pollutant with complex components. After entering the body through respiration, PM2.5 can not only cause respiratory diseases, but also break through the blood–testis barrier and influence the reproductive system. PM2.5 with different components may result in different toxic effects. In the first five years of Nanjing Jiangbei New Area, industrial transformation would change the concentration and chemical fraction of PM2.5 in the local environment to a certain extent. In this study, PM2.5 colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…The WSOC was moderately and strongly correlated with secondary inorganic ions at the Beijing (0.6 < r < 0.8) and Gwangju (0.6 < r < 0.9) sites, respectively. In other studies, secondary aerosols have been reported to contribute to an increase in OP [ 11 ] and biological responses (e.g., cell toxicity, ROS, and inflammation) [ 54 , 55 ]. Secondary inorganic ions can increase the solubility of metals in particles and change their pH (e.g., acidification) to indirectly affect OP [ 39 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The WSOC was moderately and strongly correlated with secondary inorganic ions at the Beijing (0.6 < r < 0.8) and Gwangju (0.6 < r < 0.9) sites, respectively. In other studies, secondary aerosols have been reported to contribute to an increase in OP [ 11 ] and biological responses (e.g., cell toxicity, ROS, and inflammation) [ 54 , 55 ]. Secondary inorganic ions can increase the solubility of metals in particles and change their pH (e.g., acidification) to indirectly affect OP [ 39 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NO 3 − /SO 4 2− ratio was often used to determine the main source of atmospheric particulate pollution. When the ratio was larger than 1, it meant that mobile sources, like car exhausts, dominated the emission source; when it was less than 1, it meant that stationary sources, such as coal combustion, dominated [ 4 , 30 ]. The NO 3 − /SO 4 2− ratios of the PM 2.5 samples from the residential, industrial, and traffic sources were 0.99, 1.35, and 1.30, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A common biomarker of DNA double–strand breaks (DSBs) is γ–H2AX, which is produced when H2AX is phosphorylated. The level of γ–H2AX might indicate the extent of DNA damage [ 4 , 36 ]. In this experiment, stained γ–H2AX showed green fluorescence under a fluorescence microscope ( Figure 5 a–c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations